CNS-Derived Blood Exosomes as a Promising Source of Biomarkers: Opportunities and Challenges - Hornung, Simon; Dutta, Suman; Bitan, Gal (Frontiers in Molecular Neuroscience, 2020)
Eukaryotic cells release different types of extracellular vesicles (EVs) including exosomes, ectosomes and microvesicles. Exosomes are nanovesicles, 30-200 nm in diameter, that carry cell- and cell-state-specific cargoes of proteins and nucleic acids, including mRNA and miRNA. Recent studies have shown that central nervous system (CNS)-derived exosomes may carry amyloidogenic proteins and facilitate their cell-to-cell transfer, thus playing a critical role in the progression of neurodegenerative diseases, such as tauopathies and synucleinopathies. CNS-derived exosomes also have been shown to cross the blood-brain-barrier into the bloodstream and therefore have drawn substantial attention as a source of biomarkers for various neurodegenerative diseases, as they can be isolated via a minimally invasive blood draw and report on the biochemical status of the brain. However, although isolating specific brain cell-derived exosomes from the blood is theoretically simple and the approach has great promise, practical details are of crucial importance and may compromise the reproducibility of this approach, especially when different labs use different protocols. Here, we review recent literature and discuss the role of exosomes in neurodegenerative diseases, the utility of brain-derived blood exosomes as a source of biomarkers for neurodegenerative diseases, and challenges associated with the isolation of these extracellular vesicles and subsequent biomarker analysis.